Beyond Topoisomerase Inhibition: Antitumor 1, 4‐Naphthoquinones as Potential Inhibitors of Human Monoamine Oxidase. (April 2014) - Coelho‐Cerqueira, Eduardo; Netz, Paulo A.; do Canto, Vanessa P.; Pinto, Angelo C.; Follmer, Cristian
<x xml:space="preserve">Abstract</x> Monoamine oxidase (MAO) action has been involved in the regulation of neurotransmitters levels, cell signaling, cellular growth, and differentiation as well as in the balance of the intracellular polyamine levels. Although so far obscure, MAO inhibitors are believed to have some effect on tumors progression. 1, 4‐naphthoquinone (1, 4‐NQ) has been pointed out as a potential pharmacophore for inhibition of both MAO and DNA topoisomerase activities, this latter associated with antitumor activity. Herein, we demonstrated that certain antitumor 1, 4‐NQs, including spermidine‐1, 4‐NQ, lapachol, and nor‐lapachol display inhibitory activity on human MAO‐A and MAO‐B. Kinetic studies indicated that these compounds are reversible and competitive MAO inhibitors, being the enzyme selectivity greatly affected by substitutions on 1, 4‐NQ ring. Molecular docking studies suggested that the most potent MAO inhibitors are capable to bind to the MAO active site in close proximity of flavin moiety. Furthermore, ability to inhibit both MAO‐A and MAO‐B can be potentialized by the formation of hydrogen bonds between these compounds and FAD and/or the residues in the active site. Although spermidine‐1, 4‐NQs exhibit antitumor action primarily by inhibiting topoisomerase via DNA intercalation, our findings suggest that their effect on MAO activity should be taken into account when their application in cancer therapy is considered.